Transition metal-free carboxylation of terminal alkynes with carbon dioxide through dual activation: Synthesis of propiolic acids. (July 2019) - Wang, Wan-Hui; Feng, Xiujuan; Sui, Kun; Fang, Dingqiao; Bao, Ming
Graphical abstract: Abstract: The combination use of quaternary ammonium salt and inorganic base in low-boiling-point solvent is presented as a new strategy for terminal alkyne carboxylation with CO2 . The carboxylation of terminal alkyne with CO2 proceeded smoothly in the presence of tetra- n -butylammonium acetate and K2 CO3 through dual activation under relatively mild conditions to produce the corresponding propiolic acids in satisfactory to excellent yields.